2016
DOI: 10.18632/oncoscience.323
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the SWI/SNF ATPase subunits BRM and BRG1 drives lung cancer development

Abstract: Inactivation of Brg1 and Brm accelerated lung tumor development, shortened tumor latency, and caused a loss of differentiation. Tumors with Brg1 and/or Brm loss recapitulated the evolution of human lung cancer as observed by the development of local tumor invasion as well as distal tumor metastasis, thereby making this model useful in lung cancer studies. Brg1 loss contributed to metastasis in part by driving E-cadherin loss and Vimentin up-regulation. By changing more than 6% of the murine genome with the dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…Although BRG1‐KD in ESCs and in GICs has been reported to reduce proliferation , BRG1 loss also has been shown to increase the proliferation of some cell lines . Consistent with the latter reports, we found that BRG1‐KD enhanced proliferation of both GBM6 and X16 GICs.…”
Section: Discussionsupporting
confidence: 91%
“…Although BRG1‐KD in ESCs and in GICs has been reported to reduce proliferation , BRG1 loss also has been shown to increase the proliferation of some cell lines . Consistent with the latter reports, we found that BRG1‐KD enhanced proliferation of both GBM6 and X16 GICs.…”
Section: Discussionsupporting
confidence: 91%
“…In these cases, BRM loss occurs because of epigenetic silencing of SMARCA2 locus, 30,39 and the resultant BRM loss has been demonstrated to paradoxically potentiate epithelial to mesenchymal transition and sarcomatoid transformation. 9,36 Interestingly, Rekhtman et al 18 recently described 2 BRG1-deficient tumors with sharply delineated sarcomatoid areas wherein only the sarcomatoid areas showed loss of BRM, supporting this hypothesis. Epigenetic repression of SMARCA2 appears to be reversible with EZH2 inhibitors, and SMARCA4mutant NSCLC cell lines with decreased SMARCA2 mRNA and BRM loss show a fall in proliferative activity when treated with EZH2 inhibitors.…”
Section: Discussionmentioning
confidence: 90%
“…28 BRG1 loss appears to result in failure of ATPasedependent eviction of polycomb recessive complexes, leading to widespread chromatin reorganization and changes in the expression levels of many genes implicated in the etiology of NSCLC. [34][35][36] In mouse models, heterozygous SMARCA4-knockout mice develop lung adenomas, suggesting that loss of even one SMARCA4 allele is sufficient for tumor initiation. 30 Biallelic SMARCA4 knockout, however, causes apoptosis of normal lung cells and loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Known chromatin remodelers with functional roles in EMT ( Figure 5) have been reviewed see (174) and include the NuRD subunits MTA1 and MTA3 within the CHD family, the BPTF subunit of the ISWI family member NURF (116), and the BAF250/ARID1, BRG1, and hBRM subunits of the mammalian SWI/SNF complex (174,175). Interestingly, the combined loss of BAF250A/ARID1A and gain of expressed mutated PI3K subunit PIK3CA H1047R results in partial EMT in the endometrial epithelium (176).…”
Section: Remodeling Our Understanding Of Chromatin Machinery In Emtmentioning
confidence: 99%